High-oxygen-permeability ionomer as well as preparation method and application thereof

Through the combination of high oxygen permeable ionomer and platinum carbon catalyst, the oxygen mass transfer resistance of the catalytic layer is reduced, the performance of the fuel cell is improved, the problem of large oxygen mass transfer resistance in the prior art is solved, and a higher Oxygen transmittance and power density.

CN119119363APending Publication Date: 2024-12-13DONGFENG MOTOR GRP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411122900.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The oxygen mass transfer resistance in the catalytic layer of existing fuel cells is relatively large, which affects performance, especially under high current density conditions, resulting in a decrease in membrane electrode performance.

Method used

Highly permeable ionomers are used to reduce crystallinity and density through the copolymer structure, increase gaps between molecular chain segments, improve oxygen transmittance, and prepare catalyst slurry with platinum carbon catalyst and alcohol solvent to form low oxygen resistance catalysis layer.

Benefits of technology

It significantly reduces the oxygen mass transfer resistance, improves the oxygen transmittance of the membrane electrode and the power density of the fuel cell, and improves the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119363A_ABST
    Figure CN119119363A_ABST
Patent Text Reader

Abstract

The invention relates to a high-oxygen-permeability ionomer, the high-oxygen-permeability ionomer is a copolymer, the high-oxygen-permeability ionomer is formed by mutually connecting a first structural unit and a second structural unit, the knot # imgabs 0 # of the first structural unit, and the structure of the second structural unit is # imgabs 1 #. The high-oxygen-permeability ionomer provided by the invention, the second structural unit comprises a cyclic structure, and the cyclic structure is a cyclic structure. The cyclic structure can greatly reduce the crystallinity and compactness of the high-oxygen-permeability ionomer on the premise of maintaining the chemical stability of the whole perfluoro structure of the high-oxygen-permeability ionomer, so that gaps between molecular chain segments of the high-oxygen-permeability ionomer are larger, oxygen molecules can penetrate through the high-oxygen-permeability ionomer, and the oxygen permeability of the high-oxygen-permeability ionomer is improved. Therefore, the oxygen resistance of the high-oxygen-permeability ionomer is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cells, and in particular to catalyst layer modification materials. Background Art

[0002] In recent years, proton exchange membrane fuel cells have begun their commercialization process. In particular, fuel cells increase their energy capacity without significantly increasing their weight, making them more advantageous than lithium batteries in heavy-duty vehicle applications. Heavy-duty vehicle applications require fuel cells to provide greater power and current density. However, under high current density conditions, the oxygen transport resistance of the membrane electrode cathode catalyst layer has a significant impact on fuel cell performance.

[0003] The oxygen transmission resistance of the catalytic layer mainly comes from the dissolution and diffusion resistance of oxygen in the perfluorosulfonic acid resin ionomer film covered by the platinum surface in the platinum-carbon catalyst, that is, the local oxygen transmission resistance. At the same time, an important way to reduce the cost of membrane electrodes is to reduce the amount of precious metal catalyst platinum, but when the catalyst platinum sites are reduced, the local oxygen transmission resistance in the catalytic layer will also increase sharply.

[0004] At present, the proton exchange membrane used in most membrane electrode products and the ionomer used to conduct protons in the catalyst layer are made of the same material, perfluorosulfonic acid resin. The structure of this resin is a polytetrafluoroethylene main chain connected to a side chain with a sulfonate group at the end. However, perfluorosulfonic acid resin is relatively dense and can play a good role in isolating the positive and negative polar gases in proton membrane applications. However, in the catalyst layer, perfluorosulfonic acid resin will tightly wrap the platinum carbon catalyst, thereby hindering the transfer of oxygen in the catalyst layer and forming a large local oxygen mass transfer resistance. Summary of the invention

[0005] The embodiments of the present application provide a high oxygen permeability ionomer and a preparation method and application thereof to solve the technical problem that the ionomer used in the catalytic layer has a large oxygen mass transfer resistance.

[0006] In a first aspect, an embodiment of the present application provides a high oxygen permeability ionomer, wherein the high oxygen permeability ionomer is a copolymer, and the high oxygen permeability ionomer is formed by interconnecting a first structural unit and a second structural unit.

[0007] The structure of the first structural unit is

[0008] The structure of the second structural unit is

[0009] In some embodiments of the present application, in the high oxygen permeability ionomer, the molar ratio of the first structural unit to the second structural unit is 10:1-100.

[0010] In a second aspect, an embodiment of the present application provides a method for preparing a high oxygen permeability ionomer, the method for preparing a high oxygen permeability ionomer comprising the following steps:

[0011] copolymerizing compound A and compound B to obtain an ionomer precursor,

[0012] The ionomer precursor is soaked in a strong base and a strong acid in sequence to obtain the high oxygen permeability ionomer.

[0013] Wherein, the structural formula of the compound A is The structural formula of the compound B is

[0014] In some embodiments of the present application, the copolymerization of compound A and compound B comprises the following steps:

[0015] Adding compound A, compound B and an initiator into hexafluorobenzene to obtain a mixed solution;

[0016] After degassing the mixed solution, a polymerization reaction is performed to obtain a product solution;

[0017] Dichloromethane was added as a poor solvent to the product solution, and the precipitate was collected to obtain an ionomer precursor.

[0018] In some embodiments of the present application, the polymerization reaction is carried out at 55-65° C.; and / or,

[0019] The strong base is sodium hydroxide, and the strong acid is sulfuric acid; and / or,

[0020] The compound A and the compound B are copolymerized, and the molar ratio of the compound A to the compound B is 10:1-100.

[0021] In some embodiments of the present application, the method for preparing compound A comprises the following steps:

[0022] Preparation of perfluoropyruvate fluoride by reaction of hexafluoropropylene oxide and benzophenone;

[0023] Perfluoro(2,4-dimethyl-2-fluoroformyl-1,3-dioxolane) was prepared by reacting perfluoropyruvate fluoride, cesium fluoride, and diethylene glycol dimethyl ether;

[0024] The compound A is prepared by reacting perfluoro(2,4-dimethyl-2-fluorocarbonyl-1,3-dioxolane) and sodium carbonate.

[0025] In a third aspect, an embodiment of the present application provides a catalyst slurry, wherein the catalyst slurry comprises a platinum-carbon catalyst, a highly oxygen-permeable ionomer, water, and an alcohol solvent.

[0026] in,

[0027] The high oxygen permeability ionomer is the high oxygen permeability ionomer described in any embodiment of the first aspect, or the high oxygen permeability ionomer prepared by the method described in any embodiment of the second aspect,

[0028] The alcohol solvent is at least one of ethanol, n-propanol or isopropanol.

[0029] In some embodiments of the present application, the solid content of the catalyst slurry is 8% to 11%, the mass ratio of the high oxygen permeability ionomer to the carbon carrier of the platinum carbon catalyst is 0.7 to 1:1, and the volume ratio of the water to the alcohol solvent is 1 to 4:1.

[0030] In a fourth aspect, an embodiment of the present application provides a membrane electrode, the membrane electrode comprising a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer respectively arranged on both sides of the proton exchange membrane, a cathode gas diffusion layer arranged on the cathode catalyst layer, and an anode gas diffusion layer arranged on the anode catalyst layer.

[0031] in,

[0032] The material of the cathode catalyst layer is formed by the catalyst slurry described in any embodiment of the third aspect.

[0033] In a fifth aspect, an embodiment of the present application provides a fuel cell, comprising the membrane electrode described in any embodiment of the fourth aspect.

[0034] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0035] In the highly oxygen permeable ionomer provided in the embodiment of the present application, the second structural unit comprises a ring structure, which can significantly reduce the crystallinity and density of the highly oxygen permeable ionomer while maintaining the chemical stability of the overall perfluorinated structure of the highly oxygen permeable ionomer, thereby making the gaps between the molecular segments of the highly oxygen permeable ionomer larger, which is conducive to the passage of oxygen molecules, thereby reducing the oxygen resistance of the highly oxygen permeable ionomer. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0038] Figure 1 XRD wide-angle test spectra of the high oxygen permeability ionomer in Example 1 of the present application and the nafion used in the comparative example;

[0039] Figure 2 The cell voltage-current density curves of the fuel cells assembled by the membrane electrodes in Examples 2 to 4 and Comparative Examples;

[0040] Figure 3 The power density-current density curves of the fuel cells assembled by the membrane electrodes in Examples 2 to 4 and the comparative example are shown. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0042] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.

[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0044] The existing ionomers used in the catalyst layer have the technical problem of large oxygen mass transfer resistance.

[0045] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:

[0046] In a first aspect, an embodiment of the present application provides a high oxygen permeability ionomer, wherein the high oxygen permeability ionomer is a copolymer, and the high oxygen permeability ionomer is formed by interconnecting a first structural unit and a second structural unit.

[0047] The structure of the first structural unit is

[0048] The structure of the second structural unit is

[0049] In the present application, the second structural unit comprises a cyclic structure, which can significantly reduce the crystallinity and density of the high oxygen permeability ionomer while maintaining the chemical stability of the overall perfluorinated structure of the high oxygen permeability ionomer, thereby making the gaps between the molecular segments of the high oxygen permeability ionomer larger, which is conducive to the passage of oxygen molecules, thereby reducing the oxygen resistance of the high oxygen permeability ionomer.

[0050] It is easy to understand that the high oxygen permeability ionomer is a copolymer, so the arrangement of the first structural unit and the second structural unit is not regular, but random and disordered. This random and disordered arrangement is also conducive to reducing the crystallinity and density of the high oxygen permeability ionomer.

[0051] The molecular formula of the high oxygen permeability ionomer can be represented by Formula I:

[0052]

[0053] Where X and Y are both positive integers with random values. The values ​​of X in the chain segments may be the same or different. The values ​​of Y in the chain segments may be the same or different.

[0054] In some embodiments of the present application, in the high oxygen permeability ionomer, the molar ratio of the first structural unit to the second structural unit is 10:1-100.

[0055] It is easy to understand that the first structural unit contains a side chain with a sulfonic acid group, which can provide the high oxygen permeability ionomer with the ability to conduct protons and improve the solubility of the high oxygen permeability ionomer. The second structural unit contains an oxygen-containing cyclic structure, which can increase the free volume of the high oxygen permeability ionomer and improve the oxygen permeability of the high oxygen permeability ionomer. The beneficial effect of the molar ratio of the first structural unit to the second structural unit being 10:1 to 100 is that it can ensure that the high oxygen permeability ionomer has good solubility and proton conduction ability, and also make the high oxygen permeability ionomer have a high oxygen permeability.

[0056] In a second aspect, an embodiment of the present application provides a method for preparing a high oxygen permeability ionomer, the method for preparing a high oxygen permeability ionomer comprising the following steps:

[0057] S1: copolymerizing compound A and compound B to obtain an ionomer precursor,

[0058] S2: soaking the ionomer precursor in a strong base and a strong acid in sequence to obtain the high oxygen permeability ionomer.

[0059] Wherein, the structural formula of the compound A is The structural formula of the compound B is

[0060] It is easy to understand that after the compound A and the compound B are polymerized, the -SO2F group can be treated into a -SO3H group by a strong base or a strong acid.

[0061] In some embodiments of the present application, the copolymerization of compound A and compound B comprises the following steps:

[0062] S11: adding compound A, compound B and an initiator into hexafluorobenzene to obtain a mixed solution;

[0063] S12: after degassing the mixed solution, performing a polymerization reaction to obtain a product solution;

[0064] S23: adding dichloromethane as a poor solvent to the product solution, collecting the precipitate, and obtaining an ionomer precursor.

[0065] In some embodiments of the present application, the polymerization reaction is carried out at 55-65° C.; and / or,

[0066] The strong base is sodium hydroxide, and the strong acid is sulfuric acid; and / or,

[0067] The compound A and the compound B are copolymerized, and the molar ratio of the compound A to the compound B is 10:1-100.

[0068] In some embodiments of the present application, the method for preparing compound A comprises the following steps:

[0069] S01: Preparation of perfluoropyruvic acid fluoride by reaction of hexafluoropropylene oxide and benzophenone;

[0070] S02: preparing perfluoro(2,4-dimethyl-2-fluoroformyl-1,3-dioxolane) by reacting perfluoropyruvic acid fluoride, cesium fluoride, and diethylene glycol dimethyl ether;

[0071] S03: Compound A is prepared by reacting perfluoro(2,4-dimethyl-2-fluoroformyl-1,3-dioxolane) and sodium carbonate.

[0072] The synthetic route involved in the above steps is:

[0073]

[0074] In a third aspect, an embodiment of the present application provides a catalyst slurry, wherein the catalyst slurry comprises a platinum-carbon catalyst, a highly oxygen-permeable ionomer, water, and an alcohol solvent.

[0075] in,

[0076] The high oxygen permeability ionomer is the high oxygen permeability ionomer described in any embodiment of the first aspect, or the high oxygen permeability ionomer prepared by the method described in any embodiment of the second aspect,

[0077] The alcohol solvent is at least one of ethanol, n-propanol or isopropanol.

[0078] The catalyst slurry is realized based on the high oxygen permeability ionomer described in any embodiment of the first aspect, or the preparation method of the high oxygen permeability ionomer described in any embodiment of the second aspect. The specific implementation of the catalyst slurry can refer to the above embodiments and common knowledge in the art. Since the catalyst slurry adopts part or all of the technical solutions of the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0079] In some embodiments of the present application, the solid content of the catalyst slurry is 8% to 11%, the mass ratio of the high oxygen permeability ionomer to the carbon carrier of the platinum carbon catalyst is 0.7 to 1:1, and the volume ratio of the water to the alcohol solvent is 1 to 4:1.

[0080] In a fourth aspect, an embodiment of the present application provides a membrane electrode, the membrane electrode comprising a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer respectively arranged on both sides of the proton exchange membrane, a cathode gas diffusion layer arranged on the cathode catalyst layer, and an anode gas diffusion layer arranged on the anode catalyst layer.

[0081] in,

[0082] The material of the cathode catalyst layer is formed by the catalyst slurry described in any embodiment of the third aspect.

[0083] The membrane electrode is realized based on the catalyst slurry described in any embodiment of the third aspect. The specific implementation of the membrane electrode can refer to the above embodiments and common knowledge in the field. Since the membrane electrode adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0084] In a fifth aspect, an embodiment of the present application provides a fuel cell, comprising the membrane electrode described in any embodiment of the fourth aspect.

[0085] The fuel cell is realized based on the membrane electrode described in any embodiment of the fourth aspect. The specific implementation of the fuel cell can refer to the above embodiments and common knowledge in the field. Since the fuel cell adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0086] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0087] Example 1

[0088] First, this embodiment provides compound A and compound B,

[0089] The structural formula of the compound A is The structural formula of the compound B is

[0090] The compound A is obtained by self-preparation, and the compound B is obtained by commercial purchase.

[0091] Then, this embodiment provides a high oxygen permeability ionomer, which is prepared by the following method:

[0092] Add compound A, compound B and initiator into hexafluorobenzene in a mass ratio of 1:1:0.01 to obtain a mixed solution;

[0093] The mixed solution was added to a thick-walled glass ampoule. After degassing the reaction mixture by three freeze-pump-thaw cycles with liquid nitrogen, the ampoule was sealed under vacuum and heated to 60° C. to initiate a polymerization reaction, thereby obtaining a product solution;

[0094] adding dichloromethane as a poor solvent to the resultant solution, collecting the precipitate by vacuum filtration to obtain an ionomer precursor;

[0095] After thoroughly washing the ionomer precursor with dichloromethane to remove unreacted monomers, the ionomer precursor was vacuum dried at 70° C. for 24 hours;

[0096] After the ionomer precursor is sequentially soaked in a 25 wt % sodium hydroxide solution, a first solid is collected by vacuum filtration, the first solid is then washed with water and vacuum dried at 70° C. for 12 hours;

[0097] The first solid is added to a 25wt% sulfuric acid solution and stirred at 85°C for 12 hours, and a second solid is collected by vacuum filtration. The second solid is then rinsed with water and the first solid is vacuum dried at 70°C for 12 hours to obtain the high oxygen permeability ionomer.

[0098] The preparation steps of compound A described in this example are as follows:

[0099] Commercially available hexafluoropropylene oxide (428-59-1) was used to place 200g of benzophenone in a 500ml three-necked flask, which was simultaneously connected to a gas inlet pipe, a mechanical stirrer and a gas outlet pipe. The gas outlet pipe was connected to two cold traps in series. During the reaction, the first cold trap was maintained at -10°C and the second cold trap was maintained at -80°C. The reaction flask was heated and maintained at 225°C while hexafluoropropylene oxide was passed through the vigorously stirred benzophenone at a rate of 80mL / min. The reaction was stopped after 5h. The reaction product of the collectors in the two cold traps was 150g. The mixed product consisted of a small amount of trifluoroacetyl fluoride, about 30g of unreacted hexafluoropropylene epoxide, and the rest was perfluoropyruvic acid fluoride. Perfluoropyruvic acid fluoride was purified by fractionation. The boiling point of the purified product was 9°C to 10°C.

[0100] The procedure for preparing perfluoro(2,4-dimethyl-2-fluorocarbonyl-1,3-dioxolane) is as follows: 3 g of cesium fluoride and 20 ml of diethylene glycol dimethyl ether are placed in a 200 ml flask equipped with a magnetic stirrer. The flask is cooled to 0°C and 44 g of perfluoropyruvic acid fluoride is added. The reaction mixture is maintained at 0°C and 50.6 g of hexafluoropropylene oxide is gradually added. The reaction mixture is then transferred to a steel-lined autoclave and heated at a temperature of 140°C for 5 hours. The lower layer of the resulting product is distilled to obtain perfluoro(2,4-dimethyl-2-fluorocarbonyl-1,3-dioxolane) with a boiling point of 60.5°C and a yield of 70%.

[0101] In a nitrogen stream, perfluoro(2,4-dimethyl-2-fluoroformyl-1,3-dioxolane) is passed through a loosely packed bed filled with dry sodium carbonate, and the temperature is maintained at 295°C. Nitrogen is added at a rate of 100 ml per minute. The condensed reaction product obtained in the cold trap is perfluoro(2-methylene-4-methyl-1,3-dioxolane), compound A.

[0102] Example 2

[0103] This embodiment provides a membrane electrode, which is prepared by the following method:

[0104] The high oxygen permeability ionomer obtained in Example 1, the platinum carbon catalyst with a platinum content of 47%, isopropanol and water were prepared into a catalyst slurry according to the ratio of 9% solid content of the slurry, 0.8:1 mass ratio of the carbon carrier of the ionomer platinum carbon catalyst, and 4:1 water-alcohol ratio. The catalyst slurry was dispersed by ball milling and coated on PTFE to form a catalytic layer, and then hot-pressed on the proton membrane at a high temperature of 180°C, and gas diffusion layer carbon paper was added on both sides to prepare a membrane electrode.

[0105] Example 3

[0106] The high oxygen permeability ionomer obtained in Example 1, the platinum carbon catalyst with a platinum content of 47%, isopropanol and water were prepared into a catalyst slurry according to the ratio of 7% solid content of the slurry, 0.7:1 mass ratio of the carbon carrier of the ionomer platinum carbon catalyst, and 2:1 water-alcohol ratio. The catalyst slurry was dispersed by ball milling and coated on PTFE to form a catalytic layer, and then hot-pressed on the proton membrane at a high temperature of 180°C, and gas diffusion layer carbon paper was added on both sides to prepare a membrane electrode.

[0107] Example 4

[0108] The high oxygen permeability ionomer obtained in Example 1, the platinum carbon catalyst with a platinum content of 47%, isopropanol and water were prepared into a catalyst slurry according to the ratio of 10% solid content of the slurry, 1:1 mass ratio of carbon carrier of ionomer platinum carbon catalyst, and 1:1 water-alcohol ratio. The catalyst slurry was dispersed by ball milling and coated on PTFE to form a catalytic layer, and then hot-pressed on the proton membrane at a high temperature of 180°C, and gas diffusion layer carbon paper was added on both sides to prepare a membrane electrode.

[0109] Comparative Example 1

[0110] The difference between this comparative example and Example 2 is only that:

[0111] The ionomer in the catalyst slurry used in this comparative example contained only nafion (perfluorosulfonic acid resin).

[0112] Related experiments and effect data:

[0113] The high oxygen permeability ionomer obtained in Example 1 and the nafion used in Comparative Example 1 were directly characterized by XRD wide-angle spectra. The results are as follows: Figure 1 The results show that the high oxygen permeability ionomer has a smaller polymer X-ray diffraction crystallization peak angle than the traditional perfluorosulfonic acid resin Nafion, which means that the polymer crystallinity of the high oxygen permeability ionomer is lower. Because the five-membered ring structure in the high oxygen permeability ionomer has a certain rigidity, the polymer cannot undergo a large range of twisting and movement, resulting in a decrease in crystallinity and a larger free volume, which is beneficial to its oxygen transport in the membrane electrode catalyst layer of the fuel cell.

[0114] The membrane electrodes prepared in Examples 2, 3, 4 and Comparative Example 1 were assembled into fuel cells, and polarization curves were tested under the conditions that the hydrogen to air stoichiometric ratios were 1.5 and 4.0, respectively. The polarization curves and power density curves are shown in FIG. Figure 2 and Figure 3 .

[0115] from Figure 2It can be found that the open circuit voltage of Comparative Example 1 is lower, and the voltage drops too fast during the process of current increase. This is because the resin in its catalyst layer is traditional nafion, and the oxygen mass transfer capacity is much lower than the high oxygen permeability ionomer synthesized in the present invention. In Examples 2, 3, and 4, no matter what slurry parameters are used, the membrane electrode performance is much higher than that of Comparative Example 1. Among them, the performance of Example 1 is the best, because its suitable I / C ratio and water-alcohol ratio can make the high oxygen permeability ionomer in the catalyst layer form the optimal state, which not only maintains its proton conductivity but also has a higher oxygen mass transfer capacity.

[0116] from Figure 3 It can be seen that, thanks to the high oxygen mass transfer capacity of the high oxygen permeability ionomer, at a current density of 2400 mA / cm2, Comparative Example 1 can only achieve a power density of 1424 mW / cm2, while Examples 2, 3, and 4 can achieve power densities of 1555, 1524, 1537, and 1424 mW / cm2, respectively.

[0117] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0118] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, and c can be single or multiple, respectively.

[0119] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A high oxygen permeability ionomer, characterized in that: The high oxygen permeability ionomer is a copolymer, and the high oxygen permeability ionomer is formed by interconnecting a first structural unit and a second structural unit. The structure of the first structural unit is The structure of the second structural unit is 2. The high oxygen permeability ionomer according to claim 1, characterized in that In the high oxygen permeability ionomer, the molar ratio of the first structural unit to the second structural unit is 10:1-100.

3. A method for preparing a high oxygen permeability ionomer, characterized in that: The preparation method of the high oxygen permeability ionomer comprises the following steps: copolymerizing compound A and compound B to obtain an ionomer precursor, The ionomer precursor is sequentially immersed in a strong base and a strong acid to obtain the high oxygen permeability ionomer. Wherein, the structural formula of the compound A is The structural formula of the compound B is 4. The method for preparing a highly oxygen permeable ionomer according to claim 3, characterized in that: The method of copolymerizing compound A and compound B comprises the following steps: Adding compound A, compound B and an initiator into hexafluorobenzene to obtain a mixed solution; After degassing the mixed solution, a polymerization reaction is performed to obtain a product solution; Dichloromethane was added as a poor solvent to the product solution, and the precipitate was collected to obtain an ionomer precursor.

5. The method for preparing a high oxygen permeability ionomer according to claim 4, characterized in that: The polymerization reaction is carried out at 55-65° C.; and / or, The strong base is sodium hydroxide, and the strong acid is sulfuric acid; and / or, The compound A and the compound B are copolymerized, and the molar ratio of the compound A to the compound B is 10:1-100.

6. The method for preparing a high oxygen permeability ionomer according to claim 3, characterized in that: The preparation method of compound A comprises the following steps: Preparation of perfluoropyruvate fluoride by reaction of hexafluoropropylene oxide and benzophenone; Perfluoro(2,4-dimethyl-2-fluoroformyl-1,3-dioxolane) was prepared by reacting perfluoropyruvate fluoride, cesium fluoride, and diethylene glycol dimethyl ether; The compound A is prepared by reacting perfluoro(2,4-dimethyl-2-fluorocarbonyl-1,3-dioxolane) and sodium carbonate.

7. A catalyst slurry, characterized in that: The catalyst slurry includes a platinum-carbon catalyst, a high oxygen permeability ionomer, water, and an alcohol solvent. in, The high oxygen permeability ionomer is the high oxygen permeability ionomer described in any one of claims 1 to 2, or the high oxygen permeability ionomer prepared by the method described in any one of claims 3 to 6, The alcohol solvent is at least one of ethanol, n-propanol or isopropanol.

8. The catalyst slurry according to claim 7, characterized in that The solid content of the catalyst slurry is 8% to 11%, the mass ratio of the high oxygen permeability ionomer to the carbon carrier of the platinum carbon catalyst is 0.7 to 1:1, and the volume ratio of the water to the alcohol solvent is 1 to 4:

1.

9. A membrane electrode, characterized in that: The membrane electrode comprises a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer respectively arranged on both sides of the proton exchange membrane, a cathode gas diffusion layer arranged on the cathode catalyst layer, and an anode gas diffusion layer arranged on the anode catalyst layer. in, The material of the cathode catalyst layer is formed from the catalyst slurry according to claim 7 or 8.

10. A fuel cell, characterized in that: The fuel cell comprises the membrane electrode according to claim 9.

Citation Information

Cited By

  • Method and system for preparing trifluoropyruvate by supergravity method

    CN122355825A